ANALISIS TIMBAL (Pb) DAN KADMIUM (Cd) PADA KERANG BULUYANG DIPEROLEH DARI PASAR SEI SIKAMBING MEDAN SECARA KUALITATIF - Siti Maimunah; Artha Yuliana Sianipar; Zuhairiah Zuhairiah; Setiawati Gea (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Shellfish (Anadaraantiquata) is one type of shellfish that has the potential to be used as a food source in fulfilling the nutrition of the Indonesian people. Feather clams (Anadaraantiquata) belong to the class Bivalvia which are edible and have economic value. The purpose of this study was to determine the content of lead and cadmium in feather shells. Samples were taken from two fur shell traders at the Sei Sikambing market in Medan using a random sampling method with qualitative testing using disodium sulfide, potassium iodide, potassium chromate, potassium cyanide, and sodium hydroxide reagents, in accordance with work procedures. used in the Medan Regional Health Laboratory. The results showed that of the two samples tested, both samples did not contain lead (Pb) and cadmium (Cd). Keywords: Feather shells, lead (Pb), Cadmium (Cd), Qualitative.